ANALISIS PERANCANGAN SISTEM PADA UMKM FASHION BRAND - Annisa Nadiyah Rahmani; Yudha Dwi Nugraha (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This research aims to determine adequate system design for Fashion Brand MSMEs in the city of Bandung. The research aims to improve the system implemented by the company in conducting initial document checks, interview observations, and checking company report output. The system improvements that will be repaired are directed according to the company's needs, the company's vision and mission. System design is measured using the Building Blocks, Problem Statement and System Improvement Design methods. This research is a descriptive study with a qualitative approach because the data is processed based on internal company data obtained by researchers. The research object here is MSMEs operating in the fashion sector, namely PT Hidup Gaya Lokabuat. The research achievement target here is designing documents, flowcharts and standard operating procedures as well as output improvements to reports from all sub-system elements in the company that are integrated with each other, the aim of which is to be implemented at PT Hidup Gaya Lokacipta.